Deriving priorities for combining measures to apply green remodeling to public libraries according to building age - Se Hyeon Lim; Sung Jin Sim; Seong Eun Kim; Yong Woo Song; Jin Chul Park (Case Studies in Thermal Engineering)
Efforts are being made in many fields to solve climate change challenges caused by carbon emissions, and the construction sector is an important driver of results. Moreover, integrated measures are being enforced with relevant national-level policies. For example, South Korea is presently implementing green remodeling projects to improve the energy efficiency of its public buildings. However, the national policy lacks an integrated passive and active system design. To partially fill this gap, this study identifies green-remodeling strategies for Korea's public libraries. Notably, passive systems (e.g., insulation and windows) strongly affected building energy efficiency prior to 2000. Afterward, active systems (e.g., cooling and heating facilities) became most effective in reducing energy and carbon emissions. As such, our study focuses on integrating the green benefits of both passive and active systems for library renovations and future architectural designs.